2018
DOI: 10.29252/beat-060405
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hyoscine on Pain, Tenderness, and Rebound Tenderness in Patients with Appendicitis: Quasi-Interventional Study

Abstract: Objective:To evaluate the effect of hyoscine on pain and tenderness, rebound tenderness and appendicitis patients before surgery and this study can be considered as the first study investigated the efficacy of hyoscine on pain, tenderness, and rebound tenderness in patients with appendicitis.  Methods:In this single-group, prospective interventional study (before-after) according to inclusion and exclusion criteria, 70 patients with pain in the right lower abdomen and typical symptoms of appendicitis were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…After four weeks of treatment, pain relief was detected in more than 75% of the patients in the HBB groups [8]. Esmaeili et al used HBB in acute appendicitis in a study of 70 patients; they found a significant decrease in pain and sensitivity [13]. Mousavi et al compared paracetamol and placebo in 107 patients diagnosed with acute appendicitis and found that the pain was significantly lower in the paracetamol group at 30 minutes, 1 hour, and 4 hours compared to placebo [14].…”
Section: Discussionmentioning
confidence: 99%
“…After four weeks of treatment, pain relief was detected in more than 75% of the patients in the HBB groups [8]. Esmaeili et al used HBB in acute appendicitis in a study of 70 patients; they found a significant decrease in pain and sensitivity [13]. Mousavi et al compared paracetamol and placebo in 107 patients diagnosed with acute appendicitis and found that the pain was significantly lower in the paracetamol group at 30 minutes, 1 hour, and 4 hours compared to placebo [14].…”
Section: Discussionmentioning
confidence: 99%